Method for preparation of biodegradable copolymer
Patent Information
- Application Number
- KR1020210061942
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-05-13
- Publication Date
- 2026-09-15
- Estimated Expiration
- 2041-05-13
Abstract
Description
Technology Field
[0001] The present invention relates to a method for manufacturing a biodegradable copolymer that can produce a poly(lactic acid-3-hydroxypropionic acid) copolymer through a simple process. Background Technology
[0003] Polylactic acid (PLA) is a plant-derived resin obtained from plants such as corn, and it is attracting attention as an eco-friendly material that possesses biodegradable properties while also exhibiting excellent tensile strength and modulus of elasticity.
[0005] Unlike conventional petroleum-based resins such as polystyrene, polyvinyl chloride, and polyethylene, it can reduce environmental pollution—a disadvantage of petroleum-based plastic products—by preventing the depletion of petroleum resources and suppressing carbon dioxide emissions. Therefore, as environmental pollution caused by waste plastics emerges as a social issue, efforts are being made to expand its scope of application to product sectors where general plastics (petroleum-based resins) were previously used, such as food packaging materials and containers, and electronic product cases.
[0007] However, compared to conventional petroleum-based resins, polylactic acid has lower impact and heat resistance, which limits its range of applications. Furthermore, its poor elongation to break properties and brittleness limit its use as a general-purpose resin.
[0009] In order to improve the above-mentioned disadvantages, research is being conducted on copolymers containing other repeating units in polylactic acid, and 3-hydroxypropionic acid (3HP) is receiving attention as a comonomer, particularly for improving elongation. In particular, lactic acid-3HP block copolymers are receiving attention, and said copolymers have the effect of improving elongation characteristics while maintaining the inherent properties of polylactic acid.
[0011] However, conventional lactic acid-3HP block copolymers have several disadvantages. There was a problem of reduced process efficiency because a multi-step reaction was applied, in which P3HP was first biosynthesized and then lactide was added to perform ring-opening polymerization, or PLA and P3HP were polymerized separately and then annealed. The problem to be solved
[0013] The present invention is intended to provide a method for effectively producing a poly(lactic acid-3-hydroxypropionic acid) copolymer in a single reactor by introducing lactic acid at a specific point in the 3-hydroxypropionic acid polymerization reaction. means of solving the problem
[0015] To solve the above problem, the present invention provides a method for manufacturing a biodegradable copolymer comprising the following steps.
[0016] First, a first step of preparing a 3-hydroxypropionic acid oligomer by polymerizing 3-hydroxypropionic acid; and
[0017] The method includes a second step of preparing a poly(lactic acid-3-hydroxypropionic acid) copolymer by adding lactic acid at the point where the number average molecular weight of the 3-hydroxypropionic acid oligomer is 5,000 to 50,000.
[0019] Conventionally, to manufacture poly(lactic acid-3-hydroxypropionic acid) copolymers, poly(3-hydroxypropionic acid) (P3HP) was biosynthesized and ring-opening polymerization was performed by adding lactide, or by polymerizing PLA (lactic acid) and P3HP separately and then annealing them in a multi-step reaction. However, this multi-step reaction not only reduced process efficiency but also generated by-products during the reaction process and made it difficult to produce high molecular weight copolymers. Specifically, cyclic oligomers, which are low molecular weight by-products, are prone to being generated during the multi-step reaction process. Since these cyclic oligomers do not undergo further condensation polymerization, they reduce the reaction yield, and additional purification processes are required to separate the by-products, which also reduces reaction efficiency.
[0020] Accordingly, the inventors discovered that by introducing lactic acid (LA) at a specific point in the polymerization reaction of 3-hydroxypropionic acid (3HP), a poly(lactic acid-3-hydroxypropionic acid) copolymer can be effectively produced in a single reactor, and thus, a poly(lactic acid-3-hydroxypropionic acid) copolymer with improved properties such as elongation and tensile strength can be produced while maintaining the inherent properties of polylactic acid, and thus completed the present invention.
[0021] The present invention will be described in detail below for each step.
[0023] (Stage 1)
[0024] According to one embodiment of the present invention, the method comprises a first step of polymerizing 3-hydroxypropionic acid to produce a 3-hydroxypropionic acid oligomer. The first step refers to a homocondensation polymerization step of 3-hydroxypropionic acid, which is a step prior to the addition of lactic acid. The 3-hydroxypropionic acid oligomer produced in the first step corresponds to a 3-hydroxypropionic acid homopolymer.
[0025] In addition, as described below, lactic acid is added at the point where the number average molecular weight of the 3-hydroxypropionic acid oligomer is 5,000 to 50,000, and a poly(lactic acid-3-hydroxypropionic acid) copolymer can be produced without generating by-products through a simple process.
[0027] The first step above involves carrying out a reaction at 80°C to 100°C and 8 mbar to 12 mbar for 110 to 130 minutes, and then increasing the temperature to 100°C to 120°C to 10 -2 The reaction can be carried out for 22 to 26 hours under vacuum conditions of torr. When polymerization is performed under these conditions, it is suitable for controlling the number-average molecular weight of the oligomer to a desired range and is desirable as it can effectively suppress the generation of by-products.
[0028] More preferably, the first step comprises carrying out the reaction for 115 to 125 minutes at 85 to 95°C and 9 to 10 mbar, and then increasing the temperature to 105°C to 115°C. -2 The reaction can be carried out for 24 hours ± 10 minutes under vacuum conditions of torr.
[0030] The first step above can be carried out in the presence of a sulfonic acid-based catalyst and a tin-based catalyst. The catalyst promotes the polymerization of 3-hydroxypropionic acid and simultaneously has the effect of suppressing the formation of cyclic oligomers during the polymerization process.
[0031] Preferably, the sulfonic acid-based catalyst is p-toluenesulfonic acid, m-xylene-4-sulfonic acid, 2-mesylenesulfonic acid, or p-xylene-2-sulfonic acid. Also preferably, the tin-based catalyst is SnCl2.
[0032] Preferably, the sulfonic acid-based catalyst is included in an amount of 0.1 mol% to 1.0 mol% relative to 3-hydroxypropionic acid. Within this range, the polymerization of 3-hydroxypropionic acid can be promoted while simultaneously suppressing the formation of cyclic oligomers. More preferably, the sulfonic acid-based catalyst is included in an amount of 0.2 mol% to 0.5 mol% relative to 3-hydroxypropionic acid.
[0033] Preferably, the tin-based catalyst is included in an amount of 0.025 mol% to 0.5 mol% relative to 3-hydroxypropionic acid. Within this range, the polymerization of 3-hydroxypropionic acid can be promoted while simultaneously suppressing the formation of cyclic oligomers. More preferably, the sulfonic acid-based catalyst is included in an amount of 0.05 mol% to 0.3 mol% relative to 3-hydroxypropionic acid.
[0035] Meanwhile, if necessary, a step of pre-treating 3-hydroxypropionic acid at 50°C to 70°C and 30 mbar to 80 mbar may be performed before the first step polymerization. Through the pre-treatment step, moisture inside the 3-hydroxypropionic acid can be removed.
[0037] (Stage 2)
[0038] According to one embodiment of the present invention, the method comprises a second step of adding lactic acid to produce a poly(lactic acid-3-hydroxypropionic acid) copolymer at a point where the number average molecular weight of the 3-hydroxypropionic acid oligomer produced during the reaction of a first step of polymerizing 3-hydroxypropionic acid to produce a 3-hydroxypropionic acid oligomer is 5,000 to 50,000. The second step is a step of producing a poly(lactic acid-3-hydroxypropionic acid) copolymer by condensation polymerization of the unreacted 3-hydroxypropionic acid monomer, the produced 3-hydroxypropionic acid oligomer, and the additionally added lactic acid.
[0039] Here, the first and second steps are performed in the same reactor, and the reaction efficiency is excellent. Since the timing of the addition of lactic acid is controlled to the aforementioned range, it is desirable to effectively produce a poly(lactic acid-3-hydroxypropionic acid) copolymer without by-products.
[0040] In the second step above, when lactic acid is added at the point where the number average molecular weight of the 3-hydroxypropionic acid oligomer is 5,000 to 50,000, the desired poly(lactic acid-3-hydroxypropionic acid) copolymer can be produced in excellent yield within a single reactor, resulting in excellent process efficiency. On the other hand, if lactic acid is added at the point where the number average molecular weight of the 3-hydroxypropionic acid oligomer is less than 5,000, the 3HP block of the final copolymer becomes too short, making it difficult to form crystals of the 3HP block copolymer; and if lactic acid is added at the point where it exceeds 50,000, the reaction time becomes too long, which may reduce reaction efficiency. Preferably, lactic acid may be additionally added at the point where the number average molecular weight of the 3-hydroxypropionic acid oligomer is 10,000 to 30,000.
[0042] Meanwhile, the term 'lactic acid' used in the present invention refers to L-lactic acid, D-lactic acid, or a mixture thereof.
[0044] The initial 3-hydroxypropionic acid introduced in the first step and the lactic acid introduced in the second step may be included in a molar ratio of 1:0.5 to 1:1.5. When included within this range, it is desirable that the final poly(lactic acid-3-hydroxypropionic acid) copolymer produced can have improved physical properties such as elongation and tensile strength while maintaining the inherent properties of polylactic acid. Preferably, they may be included in a molar ratio of 1:0.7 to 1:1.2.
[0046] The above second step can preferably be performed under the following two different process conditions.
[0047] Specifically, the second step comprises carrying out the reaction for 110 to 130 minutes at 80 to 120°C and 8 to 12 mbar, and then increasing the temperature to 160°C to 200°C to 10 -2 The reaction is carried out for 17 to 19 hours under vacuum conditions of torr; when polymerization is performed under these conditions, the generation of by-products can be suppressed, and sufficient PLA blocks are formed within the copolymer, allowing the inherent characteristics of the PLA blocks to be effectively exhibited. Additionally, preferably, after carrying out the reaction at 85°C to 115°C and for 115 to 125 minutes, the temperature is raised to 175°C to 185°C and 10 -2 The reaction can be carried out for 18 hours ± 10 minutes under vacuum conditions of torr. It is desirable to carry out the reaction under these conditions to reduce the possibility of depolymerization of PLA.
[0048] In addition, the second step comprises carrying out the reaction for 110 to 130 minutes at 80 to 120°C and 8 to 12 mbar, then increasing the temperature to 160°C to 200°C, and 10 -2The reaction is carried out for 3 to 7 hours under vacuum conditions of torr, and the temperature is reduced to 100℃ to 140℃, and 10 -2 The reaction can be carried out for 10 to 18 hours under vacuum conditions of torr. When carried out under these conditions, the molecular weight of the PLA block can be further increased through solid-state polymerization.
[0050] Meanwhile, since the second step is performed in the same reactor after the first step, the catalyst added in step 1 participates in the reaction in the second step as well. Additionally, the second step can be performed by further adding a sulfonic acid-based catalyst and a tin-based catalyst.
[0051] The above catalyst has the effect of promoting further polymerization of lactic acid with unreacted 3-hydroxypropionic acid monomers and generated 3-hydroxypropionic acid oligomers in the first step, while simultaneously suppressing the formation of by-products during the polymerization process.
[0052] Preferably, the sulfonic acid-based catalyst is p-toluenesulfonic acid, m-xylene-4-sulfonic acid, 2-mesylenesulfonic acid, or p-xylene-2-sulfonic acid. Also preferably, the tin-based catalyst is SnCl2.
[0053] Preferably, the sulfonic acid-based catalyst is added in an amount of 0.1 mol% to 1.0 mol% relative to the lactic acid added in the second step, and within this range, the formation of byproducts can be suppressed and the yield of the final copolymer can be improved. More preferably, the sulfonic acid-based catalyst is added in an amount of 0.2 mol% to 0.5 mol% relative to the lactic acid.
[0054] Preferably, the tin-based catalyst is added in an amount of 0.025 mol% to 0.5 mol% relative to lactic acid, and within this range, the formation of byproducts can be suppressed and the yield of the final copolymer can be improved. More preferably, the tin-based catalyst is added in an amount of 0.05 mol% to 0.3 mol% relative to lactic acid.
[0056] Meanwhile, if necessary, a step of pre-treating the lactic acid at 50°C to 70°C and 30 mbar to 80 mbar may be performed before the second stage polymerization. Through the pre-treatment step, moisture inside the lactic acid can be removed.
[0058] The weight-average molecular weight of the poly(lactic acid-3-hydroxypropionic acid) copolymer prepared according to one embodiment of the invention is 50,000 to 200,000, and more preferably 50,000 to 100,000. The method for measuring the weight-average molecular weight will be explained in detail in the experimental examples described below.
[0060] In addition, according to another embodiment of the present invention, an article comprising the poly(lactic acid-3-hydroxypropionic acid) copolymer is provided.
[0061] Examples of the above-mentioned items include packaging materials, films, nonwoven fabrics, etc., and when applied to such items, excellent elongation characteristics can be achieved while simultaneously compensating for brittleness. Effects of the invention
[0063] As described above, the method for manufacturing a biodegradable copolymer according to the present invention can effectively produce a poly(lactic acid-3-hydroxypropionic acid) copolymer in a single reactor by introducing lactic acid at a specific point in the 3-hydroxypropionic acid polymerization reaction. Specific details for implementing the invention
[0065] Hereinafter, embodiments of the present invention will be described in more detail in the following examples. However, the following examples are merely illustrative of embodiments of the present invention, and the content of the present invention is not limited by the following examples.
[0067] <Examples and Comparative Examples>
[0068] Example 1
[0069] (Step 1) 30 g (0.33 mol) of 3-hydroxypropionic acid (3HP), 75 mg of SnCl2 (0.1 mol% relative to 3HP), and 250 mg of p-TSA (0.4 mol relative to 3HP) were added to a reactor and reacted at 90°C and 10 mbar for 2 hours. The temperature was raised to 110°C and 10 -2 The reaction was carried out for 24 hours at a vacuum of torr. The number average molecular weight of the 3-hydroxypropionic acid oligomer obtained through the above reaction was 10,500.
[0070] (Step 2) 45 g (0.4995 mol) of lactic acid (LA), 12.5 mg of SnCl2 (0.1 mol% relative to LA), and 375 mg of p-TSA (0.4 mol% relative to LA) were added to the reactor containing the above oligomer, and the reaction was carried out at 90°C and 10 mbar for 2 hours. The temperature was raised to 180°C and 10 -2 The copolymer was obtained by carrying out the reaction for 18 hours at a vacuum of torr.
[0072] Example 2
[0073] (Step 1) 30 g (0.33 mol) of 3-hydroxypropionic acid (3HP), 75 mg of SnCl2 (0.1 mol% relative to 3HP), and 250 mg of p-TSA (0.4 mol relative to 3HP) were added to a reactor and reacted at 90°C and 10 mbar for 2 hours. The temperature was raised to 110°C and 10 -2 The reaction was carried out for 24 hours at a vacuum of torr. The number average molecular weight of the 3-hydroxypropionic acid oligomer obtained through the above reaction was 9,700.
[0074] (Step 2) 30 g (0.33 mol) of lactic acid (LA), 75 mg of SnCl2 (0.1 mol% relative to LA), and 250 mg of p-TSA (0.4 mol% relative to LA) were added to the reactor containing the above oligomer, and the reaction was carried out at 90°C and 10 mbar for 2 hours. The temperature was raised to 180°C and 10 -2The copolymer was obtained by carrying out the reaction for 18 hours at a vacuum of torr.
[0076] Comparative Example 1
[0077] (Step 1) 30 g of 3-hydroxypropionic acid (3HP), 75 mg of SnCl2, and 250 mg of p-TSA were added to a reactor and reacted at 90°C at 10 mbar for 2 hours. The temperature was raised to 110°C and 10 -2 The reaction was carried out for 6 hours at a vacuum of torr. The number average molecular weight of the 3-hydroxypropionic acid oligomer obtained through the above reaction was 2,200.
[0078] (Step 2) 45 g of lactic acid (LA), 2.5 mg of SnCl21, and 375 mg of p-TSA were added to the above reactor and reacted at 90°C at 10 mbar for 2 hours. The temperature was raised to 180°C and 10 -2 The copolymer was obtained by carrying out the reaction for 18 hours at a vacuum of torr.
[0080] <Experimental Example>
[0081] The properties of the copolymers prepared in the above examples and comparative examples were evaluated as follows.
[0083] 1) Evaluation of molecular weight characteristics
[0084] For each step copolymer prepared in the above examples and comparative examples, the weight-average molecular weight, number-average molecular weight, and polydispersity index were measured by gel permeation chromatography (GPC, Tosoh ECO SEC Elite), and the results are shown in Table 1.
[0085] Solvent: chloroform (eluent)
[0086] Flow rate: 1.0 ml / min
[0087] Column temperature: 40℃
[0088] Standard: Polystyrene (corrected by a cubic function)
[0090] 2) Evaluation of Elongation (%) Characteristics
[0091] For the copolymers prepared in the above examples and comparative examples, the elongation was measured and the results are shown in Table 1.
[0092] Specifically, for the copolymers prepared in the above examples and comparative examples, V-type specimens were prepared according to ASTM D536 using a hot-press machine (Limotem QM900S). For the prepared specimens, the elongation was measured under a load of 10 mm / s and 60 kg / f using an Instron 5982.
[0094] 3) Evaluation of Melting Point (Tm(°C))
[0095] For the copolymers prepared in the above examples and comparative examples, the melting point was measured and the results are shown in Table 1.
[0096] Specifically, for the copolymers prepared in the above examples and comparative examples, the melting point was measured using a Mettler Toledo DSC (N250 mL / min) based on measurement data for the target temperature range (-70℃ to 220℃), 1st heating (+10℃ / min), 1st cooling (-10℃ / min), and 2nd heating (+10℃ / min).
[0098] division Step 1 molecular weight Final molecular weight Thermal properties mechanical properties Mn Mw PDI Mn Mw PDI Tm(℃) Growth Rate (%) Example 1 10,500 30,400 2.9 40,100 100,200 2.5 170 107 Example 2 9,700 24,800 2.56 32,200 91,700 2.85 170 82 Comparative Example 1 2,200 4,350 1.98 42,700 127,000 2.98 NA NA
[0099] As can be seen in Table 1 above, the poly(lactic acid-3-hydroxypropionic acid) copolymer prepared by introducing lactic acid at a specific point in the 3-hydroxypropionic acid polymerization reaction within a single reactor was found to not only have excellent process efficiency but also exhibit excellent thermal properties and mechanical properties.
[0100] In the case of Comparative Example 1, a copolymer is formed within a single reactor, but the timing of the addition of lactic acid falls outside the scope of the present invention; accordingly, rather than forming block copolymers of PLA and P3HP, a random copolymer is formed. In the case of such a random copolymer, it was confirmed that it is difficult to measure the melting point and difficult to prepare a specimen in the form of gum at room temperature, making it difficult to measure the elongation as well.
Claims
Claim 1 A method for producing a biodegradable copolymer, comprising: a first step of polymerizing 3-hydroxypropionic acid to produce a 3-hydroxypropionic acid oligomer; and a second step of adding lactic acid to produce a poly(lactic acid-3-hydroxypropionic acid) copolymer when the number average molecular weight of the 3-hydroxypropionic acid oligomer is 5,000 to 50,000, wherein the first step and the second step are performed in the same reactor. Claim 2 A method for producing a biodegradable copolymer according to claim 1, wherein lactic acid is added at the point when the number average molecular weight of the 3-hydroxypropionic acid oligomer is 10,000 to 30,000. Claim 3 delete Claim 4 A method for manufacturing a biodegradable copolymer according to claim 1, wherein the 3-hydroxypropionic acid and lactic acid are included in a molar ratio of 1:0.5 to 1:1.
5. Claim 5 In claim 1, the first step comprises carrying out a reaction at 80°C to 100°C and 8 mbar to 12 mbar for 110 to 130 minutes, then raising the temperature to 100°C to 120°C and 10 -2 A method for producing a biodegradable copolymer, wherein the reaction is carried out for 22 to 26 hours under vacuum conditions of torr. Claim 6 In claim 1, the second step comprises carrying out the reaction for 110 to 130 minutes at 80°C to 120°C and 8 mbar to 12 mbar, and then increasing the temperature to 160°C to 200°C to 10 -2 A method for preparing a biodegradable copolymer, wherein the reaction is carried out for 17 to 19 hours under vacuum conditions of torr. Claim 7 In claim 1, the second step comprises carrying out the reaction for 110 to 130 minutes at 80°C to 120°C and 8 mbar to 12 mbar, and then increasing the temperature to 160°C to 200°C to 10 -2 The reaction is carried out for 3 to 7 hours under vacuum conditions of torr, and the temperature is reduced to 100℃ to 140℃, and 10 -2 A method for producing a biodegradable copolymer, wherein the reaction is carried out for 10 to 18 hours under vacuum conditions of torr. Claim 8 A method for producing a biodegradable copolymer according to claim 1, wherein the first and second steps are performed in the presence of a sulfonic acid-based catalyst and a tin-based catalyst. Claim 9 A method for producing a biodegradable copolymer according to claim 1, wherein the first step is performed in the presence of a sulfonic acid-based catalyst and a tin-based catalyst, wherein the sulfonic acid-based catalyst is included in an amount of 0.1 to 1.0 mol% with respect to 3-hydroxypropionic acid, and the tin-based catalyst is included in an amount of 0.025 to 0.5 mol% with respect to 3-hydroxypropionic acid. Claim 10 A method for producing a biodegradable copolymer according to claim 1, wherein the second step is performed in the presence of a sulfonic acid-based catalyst and a tin-based catalyst, wherein the sulfonic acid-based catalyst is added in an amount of 0.1 to 1.0 mol% with respect to lactic acid, and the tin-based catalyst is added in an amount of 0.025 to 0.5 mol% with respect to lactic acid. Claim 11 A method for producing a biodegradable copolymer according to claim 1, wherein the 3-hydroxypropionic acid and lactic acid are each independently pretreated at 50°C to 70°C and 30 mbar to 80 mbar before polymerization. Claim 12 A method for manufacturing a biodegradable copolymer according to claim 1, wherein the weight-average molecular weight of the poly(lactic acid-3-hydroxypropionic acid) copolymer manufactured above is 50,000 to 200,000.
Citation Information
Patent Citations
Copolymer resin composition, molded article, and method of producing the copolymer resin composition
JP2012087207A
Process for preparation of block copolymer
KR1020200126790A
Process for preparation of block copolymer
KR1020210031319A
